Nowa Umowa Kapitałowa a dostępność kredytów dla małych i średnich przedsiębiorstw - Bielawska, Aurelia (The New Capital Contract and the Availability of Credit for Small and Medium-Sized Companies, 2008)
The article presents the fundamental rules of Basel II, their influence on SME and accessibility for small and medium companies to bank loans. The paper also describes some important activities undertaken by enterprises for easing the relations between SME and banks and for improving the rating of the company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 62-68